2019
DOI: 10.1155/2019/4064652
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Research on Thermal Error Compensation of FOG in Deep Mining Using Uniform Mixed‐Data Design Method

Abstract: Suffered from the unsatisfied time consumption of thermal error compensation, this paper aims to realize a faster and more accurate fibre optic gyroscope (FOG) thermal error compensation plan, so that the deep-hole inclinometer using in mining which is based on FOG will make accurate measurement under external thermal field. Using uniform mixed-data design method, it is learned that the temperature compensation experiments only consumed 1/9 the time required for traditional method within the working condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In order to reduce the influence of temperature changes on the output accuracy of the fiber-optic gyroscope, the FOG error compensation experiment was used to establish a temperature compensation model between the parameters (temperature change rate, the effective refractive index, and the angular velocity) and the FOG output value, and to explore the mathematical relationship between them. Coefficients of the model require the FOG measurement probe to be tested on a three-axis quadrature calibration bench with a hightemperature thermostat, thereby obtaining a series of experimental data (Liu et al, 2019); photos of the temperature compensation experiment are shown in Fig. 25.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the influence of temperature changes on the output accuracy of the fiber-optic gyroscope, the FOG error compensation experiment was used to establish a temperature compensation model between the parameters (temperature change rate, the effective refractive index, and the angular velocity) and the FOG output value, and to explore the mathematical relationship between them. Coefficients of the model require the FOG measurement probe to be tested on a three-axis quadrature calibration bench with a hightemperature thermostat, thereby obtaining a series of experimental data (Liu et al, 2019); photos of the temperature compensation experiment are shown in Fig. 25.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Zhang, Y. et al [ 55 ] focused on the dynamic angular velocity modeling and error compensation of a single FOG over the whole temperature range and proposed a thermal error compensation method based on an orthogonal design. In 2019, Liu, Y. et al [ 56 ] proposed a FOG thermal error compensation scheme using Shupe error and improved the accuracy of thermal error compensation by using the finite-element method (FEM) and uniform mixed-data design method.…”
Section: Fog Drilling Tool Attitude Mwd Unitmentioning
confidence: 99%
“…In order to reduce the influence of temperature changes on the output accuracy of the fiber optic gyroscope, the FOG error compensation experiment was used to establish a temperature compensation model between the parameters (temperature change rate, the effective refractive index, and the angular velocity) and the FOG output value, and to explore the mathematical relationship between them. Coefficients of the model require the FOG measurement probe to be tested on a 540 three-axis quadrature calibration bench with a high-temperature thermostat, thereby obtaining a series of experimental data ( Liu et al, 2019), photos of the temperature compensation experiment are shown in figure 28. Due to the higher temperature in boreholes, up to 250°C, a metal vacuum flask was used to ensure that the internal space did not exceed 125°C degrees (Liu et al, 2016).…”
Section: Disccusionmentioning
confidence: 99%